Pollita Chiquita - Zimmermann, H. Werner (New York : Scholastic Inc., 1990)
Henny Penny and her friends are on their way to tell the king that the sky is falling when they meet a hungry fox.
Keywords: Folklore -- Juvenile literature; Folklore -- Literatura juvenil